2018
DOI: 10.5455/ijsm.acute-ischemic-stroke-turkey
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on the Acute Ischemic Stroke Patients Followed Up in the Neurology Clinic

Abstract: OBJECTIVE: Stroke is one of the most critical diseases causing severe disability and death. The incidence of ischemic stroke increases with advancing age.This study aims to identify the etiologic, epidemiological, demographic and clinical features of acute ischemic stroke patients and to contribute to acute stroke data in our country. MATERIALS AND METHODS: This is a retrospective descriptive study. We reviewed the hospital records of 200 patients who were admitted with acute ischemic stroke between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Many comorbid factors may negatively effect neurorehabilitation, according to our study we may add kinesiophobia to the list. [31][32][33][34][35][36] Few studies have been reported in the literature about kinesiophobia on low back pain, amputated patients, burn, knee osteoarthritis and orthopedic repair etc. Up to date there is no study about the importance of kinesiophobia in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many comorbid factors may negatively effect neurorehabilitation, according to our study we may add kinesiophobia to the list. [31][32][33][34][35][36] Few studies have been reported in the literature about kinesiophobia on low back pain, amputated patients, burn, knee osteoarthritis and orthopedic repair etc. Up to date there is no study about the importance of kinesiophobia in stroke patients.…”
Section: Discussionmentioning
confidence: 99%